Religious-Rational as an Epistemological Framework for Islamic Education: A Critical Review of the Thoughts of KH. A. Wahid Hasyim - Astia Arlinda; Maragustam Maragustam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Contemporary Islamic education still faces an epistemological problem in the form of a dichotomy between religious and general knowledge, which has the effect of reducing the meaning of education. Religious knowledge is often understood in a normative-dogmatic manner, while general knowledge develops within a framework of instrumental rationality with minimal value orientation. This article aims to analyze and reconstruct the religio-rational concept in the educational thought of KH. A. Wahid Hasyim as an epistemological framework for Islamic education. This research uses library research with a conceptual-philosophical analysis approach to relevant works and literature. Data are analyzed using content analysis and conceptual synthesis techniques to uncover the relationship between revelation, reason, and moral values in education. The results of the study indicate that religio-rationalism positions revelation as a source of values and ethical orientation, while reason functions as a rational instrument in understanding reality and developing knowledge. This framework rejects the epistemological dichotomy and offers a validity of truth that is not only logical and empirical, but also oriented towards social welfare and moral formation. This article concludes that religio-rationalism is a relevant epistemological foundation for the renewal of integrative, humanistic, and contextual Islamic education in facing the challenges of modernity.